Relay Selection for Cooperative NOMA Networks over Fading and Shadowing Channels - Fidan, Efendi; Kucur, Oğuz (IEEE, 2020)
In this work, a two-stage relay selection for a fixed power based cooperative non-orthogonal multiple access (NOMA) transmission technique is investigated, where a base station transmits data to two users via help of half-duplex (HD) multiple relays in accordance with service priority. It is assumed that the transmission medium is both small-scale and large-scale faded, and the amplitudes of the channel gains are independent identically generalized-K distributed (GKD). A relay subset is determined based on service priority for user 1 and, thereafter, a relay is selected to maximize data rate of user 2. Outage probability (OP) results for HD transmission and decode-and-forward (DF) protocol are provided via Monte Carlo simulation technique. Many special cases of GKD (Rayleigh, Nakagami-m, etc.) are exemplified. Findings demonstrate how severely fading and shadowing deteriorates system performance and its affect can be eliminated in case of selecting a relay out of multiple relays.
28th Signal Processing and Communications Applications Conference (SIU) -- OCT 05-07, 2020 -- ELECTR NETWORK
Keywords: NOMA; Relay Selection; Half-Duplex; Decode-and-Forward; Generalized-K